Bridging the Physical Health Gap in Mental Health Settings: A Ward-Based Multidisciplinary Educational Intervention - Andrea Nahum; Hannah Johnson; Harriet Agnew; Jessica Dorr; Dilisha Simkhada (BJPsych Open)
Aims: Adults with severe mental illness face a significantly higher risk of morbidity and premature death from preventable physical health conditions, with life expectancy reduced by 10–20 years compared with the general population. Early identification and management of physical health issues in mental health settings are crucial to reducing these disparities. We designed a Quality Improvement Project (QIP) focused on enhancing physical health outcomes through a ward-based multidisciplinary educational intervention on an acute male psychiatric unit in London.